KEMAMPUAN HIDUP KOLONI-KOLONI WERENG HIJAU Nephotettix virescens (Distant) PADA BEBERAPA GOLONGAN KETAHANAN VARIETAS PADI - Trisnaningsih Trisnaningsih; SS Siwi; MM Muhadjir; M Amir (BERITA BIOLOGI, 1999)
The experiment was carried out in the Laboratory of Rice Research Institute Bogor, on October 1996 to February 1997. The aim of the experiment was to study the survival rate and nymphal stages of these cobnies on a set group of rice varieties with different gen of resistance agains tungro disease. How far the source of resistance gen has been broken after the varieties have been planted by farmers alter several years. The source of colonies were taken from Bali, Central Java, West Java and South Sulawesi. Observation has been taken for the survival rate and the nymph period of each colony on each of varieties tested i. e. TO-Cisadane; T1-IR26; T2- Ciliwung; T3-IR 64 and T4-IR 72. The Completed Randomised Design was used to analyze the results. The results indicated that IR 72 still show resistance to N. virescens Bali colony and Centra! Java as shown from the longer of nymph periods compared to Cisadane as control variety. The survival rate was also still tow (21,66%), while on susceptible variety Cisadane reached around 66,66%. However, from West Java and South Sulawesi colonies, IR 72, no significant different has been found with Cisadane. IR26 and Ciliwung found to be resistant against colony of South Sulawesi as indicated from the low of survival rate i.e 10% and 28,33% respectively. IR 64 has been adapted for all colonies tested as shown from the higher of survival rate and the shorter of nymph's periods.